Using Norway spruce clones in Swedish forestry: introduction. Issue 5 (4th July 2019) - Rosvall, Ola; Bradshaw, Richard H.W.; Egertsdotter, Ulrika; Ingvarsson, Pär K.; Wu, Harry
ABSTRACT: In this introductory paper, we briefly review the history of using clones in Swedish forestry. The different approaches of using clones are defined as: (1) "clonal forestry", the deployment of tested selected clones, and (2) "family forestry" with vegetative multiplication of crosses between elite parents. Clones of Norway spruce may be deployed as rooted cuttings or as propagules produced via somatic embryogenesis (SE). The speed and flexibility of using clones is compared with the traditional deployment of reforestation stock raised from seed orchard seed. The key questions addressed in this special issue are presented: (1) what are the benefits and risks of using clones in forestry, (2) what physiological and genetic effects are introduced by the SE propagation technology, (3) what are the long-term genetic consequences of changing genetic diversity by using clones, (4) what are the environmental consequences of using clones, and (5) what are the management implications from vegetatively propagated nursery stock?